2021
DOI: 10.3390/healthcare9121663
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Bone Thickness in Anterior and Posterior Teeth—A Systematic Review

Abstract: (1) Background: Immediate dental implant placement has been a subject of great interest over the last decade. Here, information regarding the anatomy and bone thickness of the jaw prior to dental implant placement is crucial to increase the surgery’s success and the patient’s safety. The clinical premises for this approach have been controversially discussed. One of those heavily discussed premises is a buccal bone thickness of at least 1 mm thickness. This meta-analysis aims to systematically review buccal bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 141 publications
2
17
2
2
Order By: Relevance
“…Thin buccal bone was noted mainly at the central and lateral incisors, while a thicker buccal bone was identified at the canines, which has been reported in previous works 32,34 . Furthermore, the results obtained in this study that the average bone thickness in the maxilla and mandible at the root apex level was >1 mm, are consistent with the data in the literature 31 . However, the data in the literature should be interpreted with caution, as the reported bone thickness measurements are heterogeneous with high standard deviations.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thin buccal bone was noted mainly at the central and lateral incisors, while a thicker buccal bone was identified at the canines, which has been reported in previous works 32,34 . Furthermore, the results obtained in this study that the average bone thickness in the maxilla and mandible at the root apex level was >1 mm, are consistent with the data in the literature 31 . However, the data in the literature should be interpreted with caution, as the reported bone thickness measurements are heterogeneous with high standard deviations.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the buccal bone thickness at the level of the root apex was consistently >2 mm in the maxillary and >4 mm in the mandibular anterior region in both imaging modalities. These findings confirm the results of previous CBCT studies, which showed that buccal bone thickness in the anterior maxilla and mandible was predominantly thin at measurement points 1–9 mm to the alveolar crest, ranging from 0.4 to 0.9 mm 28,31–33 . Thin buccal bone was noted mainly at the central and lateral incisors, while a thicker buccal bone was identified at the canines, which has been reported in previous works 32,34 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is justified by the fact that the cortical layer of bone tissue of the buccal side is primarily affected by etiopathological factors, even with preserved dentition [6].…”
Section: Resultsmentioning
confidence: 99%